Understanding Underage Drinking in Peru: Determinants of Its Frequency and Intensity - Seinfeld, Janice; Galarza, Francisco (Economia, 2014)
Underage drinking is a serious problem worldwide. In the case of Peru, 50% of those who have ever used alcohol started doing so before the age of 13, and 90% before 16. In this study, we examine the correlations of frequency and intensity of underage drinking in Peru. We find that individual characteristics (smoking and carrying guns), exposure to traumatic events (sexual abuse and domestic violence), peer effects, and access to information are significantly correlated with drinking. This highlights the importance of addressing the problem in a comprehensive manner that includes students, parents, schools, and the government, especially considering that policies targeted at adolescents may have multiplier effects.